Chromium Hyper-Tolerant Bacillus sp. MH778713 Assists Phytoremediation of Heavy Metals by Mesquite Trees (Prosopis laevigata) - Ramírez, Verónica; Baez, Antonino; López, Primavera; Bustillos, Rocío; Villalobos, Miguel Ángel; Carreño, Ricardo; Contreras, José Luis; Muñoz-Rojas, Jesús; Fuentes, Luis Ernesto; Martínez, Javier; Munive, José Antonio (Frontiers in Microbiology, 2019)
Heavy metal accumulation in mesquite trees (Prosopis laevigata) growing in aluminum, titanium, chromium and zirconium-polluted soils (Al up to 61800 mg/kg) of a semi-arid region in Mexico was investigated using wavelength dispersive X-ray fluorescence analysis. The results showed that P. laevigata trees can hyperaccumulate up to 4100 mg/kg of Al, 14000 mg/kg of Fe, 1600 mg/kg of Ti, 2500 mg/kg of Zn, but not chromium, regarding high chromium concentrations found in soils (435 mg/kg). Since plant-associated microorganism can modulate phytoremediation efficiency, biodiversity of P. laevigata associated bacteria was studied. Eighty-eight isolates from P. laevigata nodules were obtained; all isolates tolerated high concentrations of Fe, Zn and Cr in vitro. The top-six chromium tolerant strains were identified by 16S rRNA sequence analysis as belonging to genus Bacillus. Bacillus sp. LEM1088 (Genbank accession number MH778713), close to Bacillus cereus group, showed to be the most resistant strain, tolerating up to 15000 mg/kg Cr(VI). Bacillus sp. LEM1088 accumulated up to 100 mg Cr(VI)/g of cells when it was exposed to 1474 mg/kg of Cr(VI), regarding the bioaccumulation traits. To assess Bacillus sp. LEM1088 ability to assist Prosopis laevigata phytoremediation; twenty plants were inoculated or non-inoculated with Bacillus sp. LEM1088 and grown in nitrogen-free Jensen’s medium added with 0, 10 and 25 mg/kg of Cr (VI). Only plants inoculated with Bacillus sp. grew in the presence of chromium showing the ability of this strain to assist chromium phytoremediation. P. laevigata and Bacillus spp. may be considered as good candidates for soil restoration of arid and semiarid sites contaminated with heavy metals.